DIAGNOSIS OF LIVER FIBROSIS IN CHRONIC VIRAL HEPATITIS C IN HIV-INFECTED CHILDREN - Isakovna, Khadieva Dora (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Chronic viral hepatitis (CH) poses a significant challenge in contemporary healthcare, leading to severe liver diseases such as cirrhosis and hepatocellular carcinoma. Specific Background: Among the known hepatotropic viruses, hepatitis B, C, D, and G are implicated in chronic liver conditions, with hepatitis C virus (HCV) being particularly concerning in co-infected populations, such as children with HIV. Knowledge Gap: While the progression of liver fibrosis in CH is well-documented, the interplay of risk factors affecting fibrosis progression in HIV-infected children remains underexplored. Aims: This study aims to assess the risk factors influencing liver fibrosis in children diagnosed with chronic hepatitis C and co-infected with HIV, emphasizing the need for timely diagnosis and management. Results: Preliminary findings indicate that HIV co-infection significantly exacerbates the progression of liver fibrosis in children with chronic hepatitis C, highlighting age, immune status, and viral load as critical factors. Novelty: This research provides novel insights into the unique clinical presentation of liver disease in pediatric HIV-positive populations, which is often overlooked in current literature. Implications: The implications of this study are profound, suggesting that healthcare providers must prioritize regular screening for liver fibrosis in this vulnerable demographic to improve clinical outcomes and inform therapeutic strategies. Addressing this issue could lead to enhanced management protocols for co-infected children, ultimately reducing morbidity associated with chronic liver disease.